Targeting EGFR-PI3K-AKT-mTOR signaling enhances radiosensitivity in head and neck squamous cell carcinoma - Horn, Dominik; Heß, Jochen; Freier, Kolja; Hoffmann, Jürgen; Freudlsperger, Christian (Expert opinion on therapeutic targets, 2015)
Introduction: Head and neck squamous cell carcinoma (HNSCC) is frequently characterized by high resistance to radiotherapy, which critically depends on both altered signaling pathways within tumor cells and their dynamic interaction with the tumor microenvironment.Areas covered: This review covers EGFR-phosphoinositide 3-kinase (PI3K)-protein kinase B (AKT)-mechanistic target of rapamycin (mTOR) signaling in HNSCC. The role of each pathway node in radioresistance is discussed. Preclinical and clinical innovative aspects of targeting EGFR-PI3K-AKT and mTOR are demonstrated. Ongoing clinical trials and future perspectives are presented.Expert opinion: Different cellular signaling pathways seem to mediate radioresistance in advanced HNSCC and various molecular targeted therapies are currently being investigated to sensitize tumor cells to radiotherapy. Recently, new insights in the mutational landscape of HNSCC unraveled critical alterations in putative oncogenes and tumor suppressor genes and have emphasized the importance of PI3K and the corresponding upstream and downstream signaling pathways in pathogenesis and treatment response. The frequent activation of the EGFR-PI3K-AKT-mTOR pathway in HNSCC and its implication in the context of radiosensitivity make this pathway one of the most promising targets in the therapy of HNSCC patients. Clinical studies targeting EGFR and mTOR in combination with radiotherapy are under investigation.